Azole susceptibility and resistance in Candida dubliniensis. (26th October 2005) - Pinjon, E.; Moran, G.P.; Coleman, D.C.; Sullivan, D.J.
Abstract : Candida dubliniensis is a recently described species of pathogenic yeast that shares many phenotypic features with Candida albicans . It is primarily associated with oral colonization and infection in HIV-infected individuals. Isolates of C. dubliniensis are generally susceptible to commonly used azole antifungal agents; however, resistance has been observed in clinical isolates and can be induced by in vitro exposure. Molecular mechanisms of azole resistance in C. dubliniensis include increased drug efflux, modifications of the target enzyme and alterations in the ergosterol biosynthetic pathway.